The evolution and toughening mechanism of austenite in high Co–Ni ultrahigh strength steel - Aijun Li; Yangxin Wang; Xiaohan Duan; Chundong Hu; Han Dong (Journal of Materials Research and Technology)
The austenite, as a “soft” phase, has a significant impact on the mechanical properties in ultrahigh strength steel. The morphology, size, and distribution of austenite play a critical role in toughness of steel. This study concentrates on morphology, size, and distribution of austenite subjected to solid solution, cryogenic, and aging treatments and explores its evolution characterized by transmission electron microscopy, scanning electron microscopy, electron backscatter diffraction and x-ray diffraction. The toughening mechanism of austenite with different characterization was investigated through charpy impact testing and fracture morphology analysis. The results indicate that filmy and blocky austenite existed at the lath boundary of martensite. Blocky austenite and some filmy austenite were eliminated after cryogenic treatment, while approximately less than 15 nm filmy reverted austenite was formed after aging treatment. Filmy reverted austenite at the boundary of martensite laths can enhance toughness. Retained austenite without cryogenic treatment can induce the formation of larger blocky austenite, which decreased toughness.